Epidemiological and pathological characteristics of post-surgical cases of invasive breast cancer among ethnicities of Iran in 2018: A single center cross-sectional study - Sayad, Soheila; Ahmadi, Seyyed Amir Yasin; Nekouian, Reza; Panahi, Mahshid; Anbari, Khatereh (Archive of Oncology, 2019)
Background: Present study aimed to investigate immunohistochemical parameters in post-surgical cases of invasive breast cancer. Methods: In this single center cross-sectional study we investigated ethnicity, familial history, type of cancer, stage of cancer, lymph node positivity, bilateral involvement, metastasis and immunohistochemical parameters (estrogen and progesterone receptor, human epidermal growth factor receptor 2, as well as frequency of triple positive and triple negative patients merely based on immunohistochemical parameters). Results: Frequency of positive familial history was 27.42% (16.31-38.52%). Lymph node involvement was detected in 55.93% (43.26-68.60%) of the cases. Frequency of positive HER2 was 38.60% (25.96-51.23%). There were 17.54% (7.67-27.42%) of triple positive and 7.02% (0.39-13.65%) of triple negative cases. The most common stage at the time of diagnosis was stage 3 with 43.33% (30.79-55.87%) frequency. In Lur/Lak population higher frequency of positive HER2 cases was detected whereas in Mazani population frequency of positive HER2 cases was low (p=0.0291). Conclusion: These results could contribute to understanding of breast cancer patterns among different ethnicities. In order to draw clear conclusion future investigations have to be done in several health centers, for longer time periods and with larger number of patients.
Keywords: Iran; pathology; triple negative; HER2; estrogen receptor; Breast cancer